Design and Experiment Research of Static Strength Test Benches for Small Modulus Plastic Gears - Cui Xing; Xin Dong; Yu Bo; Shi Zhaoyao (Jixie chuandong)
In order to obtain the static strength of small modulus plastic gears, a small modulus plastic gear static strength test bench is developed, which can accurately measure the static strength of plastic gears under different modulus, speeds and materials. The working principle, constitution and the design of tooling parts of the test bed are mainly introduced. The test bench is composed of the mechanical system, the electric control system and the measuring software. The electric control system and the measuring software mainly adopt the horizontal structure, which is of the compact structure, with small space occupation, uses simple fixture design and is easy to measure. The static strength test is carried out, and the static strength using different materials is briefly tested. The experimental equipment can realize the measurement of the static strength of the small module plastic gear, which solves the problems of inaccurate static strength test of the small module gear and the difficulty of test clamping, and provides theoretical value and practical application value for the design of the plastic gear in the future.